Improving Structural Stability and Anticoagulant Activity of a Thrombin Binding Aptamer by Aromatic Modifications. (31st January 2022) - Busschaert, Nathalie; Maity, Debabrata; Samanta, Pralok K.; English, Niall J.; Hamilton, Andrew D.
Abstract: The thrombin binding aptamer (TBA) is a 15‐mer DNA oligonucleotide (5′‐GGT TGG TGT GGT TGG‐3′), that can form a stable intramolecular antiparallel chair‐like G‐quadruplex structure. This aptamer shows anticoagulant properties by interacting with one of the two anion binding sites of thrombin, namely the fibrinogen‐recognition exosite. Here, we demonstrate that terminal modification of TBA with aromatic fragments such as coumarin, pyrene and perylene diimide (PDI), improves the G‐quadruplex stability. The large aromatic surface of these dyes can π‐π stack to the G‐quadruplex or to each other, thereby stabilizing the aptamer. With respect to the original TBA, monoPDI‐functionalized TBA exhibited the most remarkable improvement in melting temperature (ΔTm ≈+18 °C) and displayed enhanced anticoagulant activity. Abstract : The thrombin‐binding aptamer (TBA) forms a chair‐like G‐quadruplex that shows anticoagulant properties by interacting with thrombin. Modification of TBA with aromatic chromophores is shown to improve the quadruplex stability and thrombin binding affinity. The best results were obtained for the addition of a single PDI unit, which increases the thermal stability (ΔTm =+18.2 °C) and anticoagulant ability of the aptamer.